Arresting John Entick: The Monitor Controversy and the Imagined British Conquests of the Spanish Empire. (7th November 2014) - Stiles, David
Abstract This article explores the events surrounding the Monitor controversy, which stemmed from radical criticism of the crown's conservative approach to the war between Spain and Great Britain in 1762. While some observers wished to quickly bring the war to an end, others expressed more radical plans for the destruction of the Spanish Empire. When the crown retaliated against prominent agitators with a round of arrests designed to silence their dissent, the result was a succession of legal cases that culminated with Entick v. Carrington in 1765. In their arguments, the plaintiffs expressed concern that the British Empire was seemingly in danger of evolving into an oppressive, allegedly "Spanish" style of polity. These legal processes and the precedents they set were critical to the development of protected space for political dissent in the British Empire, and affirmed a more broadly participatory model for the future development of imperial policy.